(untitled) (Fiep Bulletin - online, 2011)
The present study is about an experience developed by Nursing students of UFRN working on the project "Dengue Fever, Water and Trash" as an educative practice for the course Epidemiology and Environmental Health in Family’s Health Unit (FHU) in Santa Tereza, Parnamirim/ RN. It had as subject elderly people, children, and teenagers, and, it aims: link the community to the FHU, orientate questions related to environmental health and discuss about preservation, respect and caring of the environment for a better quality of life. The participative and interactive with groups methodology were used. The discussed themes were: oral health, dengue fever , trash and diseases related to; consume and treatment of water. The methods used were adapted to the age of the participating public: puppets, lectures, discussions, movies and dynamics. It was concluded that the experience woke up the interest of groups and contributed for an approximation of the teaching/ service/ community.